Natural Xilan Production From Corncobs (Zea Mays L.) With Extraction Method - Arifan , Fahmi (KnE Social Sciences, 2019)
Corn (Zea mays L.) not only used as food by humans, however also used for animal feed and industrial materials but in part of corncobs still untapped, corncobs is a lignocellulosic material with 38,99% ﬁber which contain the highest xilan (12,4%) comparedwithotheragriculturalwaste.Theobjectiveofthisresearchwastogetxylan fromcorncobswithextractionmethod.Xylanextractionfromcorncobsweredoneintwo steps, ﬁrstly deligniﬁcation process in NaOCl with concentration 0,5 on temperature 28∘C, solids which resulting from immersion in NaOH solution with concentration 5%, 10%, 15%, and 20% for 24 hours with temperature 20, 40, and 70∘C.the resulting of ﬁltrate were neutralized with HCL 6N, futhermore centrifuge during 30 minute with 4000 rpm. Water soluble xylan can separated with ethanol 95% with ratio supernatan and ethanol 1:3, yielding 12.9% of xylan. The solubility of xylan produced with alkali (NaOH 1%), HCl 1N, ethanol, in cold and hot water was observed. Quantitative and qualitative analysis of xylan were done using HPLC by measuring retention time. The instrumen used with HPLC Shimadzu C-R3A, C18 column type, water mobile phase, Refractive index detector with ﬂow rate 0,8 ml/minute result showed with purity 96%. Keywords: xylan, corncobs, extraction